The Effect of Intradermal Injection with Two Different Injection Techniques on Pain and Functional Status in Patients with Chronic Nonspecific Neck Pain - Sadiye MURAT (Medeniyet Medical Journal)
Objective: This study aimed to compare the effectiveness of different mesotherapy techniques applied at various dermal depths on pain, functional status, and quality of life in patients with non-specific neck pain. Methods: A total of 43 patients who received mesotherapy for non-specific neck pain were retrospectively analyzed. Patients treated with the point-by-point technique (n=21) and the napaj technique (n=22) were recorded. A mixture of 2 mL lidocaine and tenoxicam was used as the mesotherapy solution. Pain was assessed using the visual analog scale (VAS), functional status was assessed using the neck disability index (NDI), and quality of life was assessed using the Nottingham health profile before (T0), after (T1), and 3 months after (T2). Results: In both groups, which were homogeneous in terms of demographic data, statistically significant changes were observed in T1 and T2 values compared with T0 for all evaluation parameters (p=0.001). While both groups demonstrated improvement in all parameters, the posttreatment VAS and NDI score in the point-by-point group was slightly better than that in the napaj group (p=0.042), (p=0.043) but this difference disappeared in the 3-month evaluation. Conclusions: Mesotherapy using a lidocaine-tenoxicam mixture with both the point-by-point and napaj techniques is an effective and safe treatment method for nonspecific neck pain. Both techniques were found to be effective in improving pain, functional status, and quality of life, but neither technique was found to be superior to the other.